(untitled) (Research, Society and Development, 2020)
Child labor is a problem of great social impact and directly affects the life and basic rights of children and adolescents who are victims of this exploitation, causing physical, psychological and educational damage, generating future losses and throughout the life of the subjects affected. Thus, the objective of this article is to carry out a reflexive analysis about the history, causes, consequences and laws that involve this social phenomenon, in Brazil and in the Legal Amazon, through a critical look, emphasizing the educational and cognitive aspects inherent to this characteristic phase of childhood. Considering that this problem is common in the daily lives of hundreds of children in the Amazon of Pará, it is necessary to pay due attention to this problem. In this sense, although there are numerous initiatives to combat this problem, it is still a persistent evil today. In this sense, many actions and social engagement are needed, which aim to eradicate the use of the work of children and adolescents, so that a truly civilized society can be experienced.